Angelica remotiserrata (Apiaceae), a new species from Turkey based on morphological and molecular data - Tuncay, Huseyin Onur; Akalin, Emine (Taylor & Francis Ltd, 2023)
Angelica remotiserrata is a novel endemic species discovered in the Kastamonu provinces of northern Turkey. The new species is described by morphological, carpological, ecological and phylogenetic analysis. A. remotiserrata is morphologically distinct from Angelica sylvestris by the coarsely serrata leaf margins, the small and not swollen sheath, the larger fruit and the 12-14 dorsal vittae. A phylogenetic analysis based on the internal transcribed spacer (ITS) sequence of the ribosomal DNA was conducted to reveal the evolutionary relationships of the new species. Its relationships with related species and proposed conservation status were reviewed. The morphological, and molecular evidence clearly supports that A. remotiserrata is a new species.
Keywords: Angelica; new species; Turkey; apiaceae; morphology; anatomy; molecular; phylogeny; >